Morphology of the ablated gall-bladder from the short-scar incision in patients with acute cholecystitis - A. V. Kapshitar (Zaporozhye State Medical University, 2015)
Aim. Acute cholecystitis is the most frequent pathology among the acute surgical diseases of abdominal cavity organs. The aim of the research was the investigation of morphological forms of acute cholecystitis and their comparison with histologycal conclusion. Methods and results. The right transrectal longitudinal short-scar incision was implemented in 134 patients and intraoperatively in 22 (16,4%) patients the catarrhal form of cholecyctitis, in 62 (46,3%) - phlegmonous form and in 50 (37,3%) - gangrenal one were confirmed. Diagnosis of acute cholecystitis was histologically confirmed in 11 (82,8%) patients, overdiagnostics took place in 23 (17,2%). Coincidence of forms of cholecystitis was in 90 (67,2%) patients, overdiagnostics was in 36 (26,8%) and underdiagnostics - in 8 (6%). Conclusion. This demonstrates that visual methods are limited for estimation of changes in the gall-blader.